Leptoceroidea (Insecta: Trichoptera: Integripalpia) from Serra do Caparaó, Southeast Brazil, including a new species of Atanatolica Mosely (Leptoceridae) - Henriques-Oliveira, Ana Lucia; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2020)
Serra do Caparaó is an impressive mountain range between the states of Minas Gerais and Espírito Santo, Southeast Brazil, inserted within the Atlantic Forest biome, and has a mosaic vegetation composed mainly by Dense Ombrophilous Forest and rupicolous vegetation of high-altitude grasslands. This study contributes to increasing the knowledge on the Leptoceroidea fauna of the Serra do Caparaó. Herein, we describe and illustrate a new species of Leptoceridae, Atanatolica bandeira sp. nov. and provide additional data on the richness and distribution of Leptoceroidea from Parque Nacional do Caparaó and surrounding areas. The distribution of some species is expanded. Fourteen and four species are recorded for the first time from Espírito Santo and Minas Gerais states, respectively.